If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 7(x + -2x) = 60 Combine like terms: x + -2x = -1x 4 + 7(-1x) = 60 Remove parenthesis around (-1x) 4 + 7 * -1x = 60 Multiply 7 * -1 4 + -7x = 60 Solving 4 + -7x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -7x = 60 + -4 Combine like terms: 4 + -4 = 0 0 + -7x = 60 + -4 -7x = 60 + -4 Combine like terms: 60 + -4 = 56 -7x = 56 Divide each side by '-7'. x = -8 Simplifying x = -8
| 2n-5n=-3 | | -4.9x+6.88x-1.25=0 | | -35-2r=-3r+4(2r-7) | | 21+8p=-2(4-p)-7 | | p-2/6=p-4 | | a+b-c=d | | 5h+2-(h)=22 | | 7=7-10x | | -4.9x+7.25x-1.25=0 | | 9+4y=2(3-1) | | 2.3+3n=0.8n+12 | | 2(x-4)+3x=4(x-5) | | 5.5-10=11 | | 106=2(-6b+5) | | =500(1.05)(9) | | 13=4p+5+4p | | 2x-27y+11xy=22 | | [x-5]=[x+2] | | 5=1-4a-8 | | 3x+y-8x+2y= | | 3(1-4x)+2(7x)=25 | | -8(4+9r)=7*(-2-11r) | | 18-5w+7w-4=28 | | 10-4h+2+5h=-12+9h | | 2(8n+9)=4(n+2) | | a-8+7=-6 | | 6y=8y-40 | | p-6/2=p-2 | | 2x-(4-x)=4[5-(4+9x-1)] | | t-17=15 | | 6.6-5=31 | | -5y-4=-2y+1 |